Respuesta :
Answer:
see explanation
Step-by-step explanation:
Given the 2 equations
3x - 5y = - 2 → (1)
2x + y = 3 → (2)
Multiply (2) by 5 will eliminate y when added to (1), that is
10x + 5y = 15 → (3)
Add (1) and (3) term by term
(3x + 10x) + (- 5y + 5y) = (- 2 + 15)
13x = 13 ( divide both sides by 13 )
x = 1
Substitute x = 1 into (2) for corresponding value of y
2 + y = 3 ⇒ y = 3 - 2 = 1
Solution is (1, 1)
The correct possible option is B) Multiply first equation by -2 and second equation by 3, solution (1, 1).
Given, set of equations are [tex]3 x - 5 y = -2[/tex] .....(1)
And [tex]2 x + y = 3[/tex]....(2)
We have to solve these equations by elimination method, so we multiply equation 1 by -2 and equation 2 by 3, we get
[tex]-6 x + 10 y = 4[/tex]......(3)
[tex]6x+3y=9[/tex]....(4)
On adding equation 3 and equation 4, we get
[tex]13y=13[/tex]
[tex]y=1[/tex]
Now put the value of [tex]y=1[/tex] in equation 3 we get,
[tex]-6x+10\times1=4[/tex]
[tex]-6x+10=4[/tex]
[tex]-6x=4-10[/tex]
[tex]-6x=-6[/tex]
[tex]x=1[/tex].
Hence we have to first multiply equation 1 by -2 and second equation by 3 so the solution of the system of equation is (1,1).
For more details on elimination method follow the link:
https://brainly.com/question/8104215